Holocene sedimentary facies in the incised valley of Ma River Delta, Vietnam - Nguyen Minh, Quang; Vu Van, Ha; Nguyen Thi, Min; Ngo Thi, Dao; Nguyen Thi Thu, Cuc; Dang Minh, Tuan; Dang Xuan, Tung; Tran Thi, Man; Nguyen Thi, Thao (Vietnam Journal of Earth Sciences, 2023)
Holocene sediment facies in the incised valley of the Ma River Delta were clarified by using analysis of LKTH6 core (32 m depth) such as sedimentary structure analysis, grain-sized, micro-paleontological (foraminifera, spore and pollen, and diatom), clay minerals characteristics, and Radiocarbon dating (14C). Ten sedimentary facies were identified, including (1) flood plain silty clay facies, (2) Salt marsh clayey silt facies, (3) Tidal flat sandy silty clay facies, (4) Tidal creek and tidal branch silty clayey sand facies, (5) Bay silty clay facies, (6) Prodelta silty clay facies, (7) Delta front silty sand facies, (8) Mouth bar sand facies, (9) Point bar silty sand faces, and (10) Alluvial plain silty clay facies. The sea level change after the last glacial was recorded by sediment facies and radiocarbon dating (14C). It showed that before 9380 yr. BP, the transgression concurrent with the base-level rising resulted in the incised valley filled up by fluvial sediment. The transgression drowned incised valley was recorded by the initial marine flooding surface which was identified by salt marsh sedimentary facies in the valley at 9380 yr. BP, and the drowning process of the incised valley completely around 8000 yr. BP. After 8000 yr. BP, the sedimentary accumulation exceeded the sea level rise rate resulting in the delta being formed.